Panchromatic Ru (II) Dipyrrins as NCS Free Sensitizers Showing Highest Efficiency for DSSCs. (20th January 2015) - Swetha, T.; Niveditha, S.; Bhanuprakash, K.; Singh, Surya Prakash
Abstract: Two new Ru(II) complexes bearing with substituted dipyrrinato ligands (GS3 andGS10 ) have been successfully synthesized and characterized. These sensitizers exhibit panchromatic light harvesting properties, rendering them promising for DSSC applications.GS3 has shown high overall power conversion efficiency (η = 2.79%) compared toGS10 which is the highest so far in the case of Ru (II) dipyrrinato dyes. Density functional theory (DFT) and time-dependent DFT calculations were measured forGS3 andGS10 to understand their structural, electronic and photophysical properties.